Heat leak term: A signature of irreversibility in analysing the actual SI engine cycle using finite-time thermodynamics - Joseph Antonio V.K.; Thampi Gireeshkumaran (FME Transactions, 2022)
Due to the headway in innovations, it ends up noticeably unavoidable to do a complex thermodynamic analysis of thermal systems. The major problem faced during the development of a thermodynamic model for the analysis is to check the feasibility of the proposed model contrasted with the current options. Finite Time Thermodynamics can be utilized adequately to meet this without going for a mind-boggling investigation. Nonetheless, if the process is divided into infinitesimally small processes with the irreversibilities accounted at all equilibrium conditions; a reversible thermodynamic approach could be utilized. This paper shows the efficacy of such an approach and the errors accompanied with while analysing the Otto cycle. The Finite Time model created in this work is investigated and contrasted with the actual values. For the thermal efficiency calculated, Finite Time Thermodynamic model was observed to be more accurate than other similar techniques that do not involve complex thermodynamic analysis. Finite Time Thermodynamic model created accounts for the entire complex phenomenon occurring in an SI engine with an introduction of only a heat leak term into it.